Evaluating Physical Infrastructure Policy for Poverty Reduction in Nias Regency - Geni Andalria Harefa; Florentina Ratih Wulandari; Sri Sediyaningsih (Golden Ratio of Social Science and Education, 2026)
Infrastructure development is a strategic fiscal instrument for poverty reduction in frontier (3T) regions, yet massive capital injections often fail to yield proportionate socio-economic benefits. This study evaluates the structural efficacy and implementation dynamics of physical infrastructure policy in Nias Regency, a disadvantaged archipelagic territory. Employing a qualitative descriptive design, data was gathered through semi-structured interviews, participant observations, and document analysis, and subsequently analyzed using William N. Dunn’s evaluation criteria alongside George C. Edward III’s implementation model. The findings reveal a distinct administrative paradox. While road network expansion effectively reduced spatial isolation decreasing isolated villages from 24 to 18 and achieving 233.89 km of reliable roads its capacity to eradicate systemic poverty remains structurally constrained. Policy performance is diluted by extreme geomorphological cost premiums (reflected in an escalating Construction Cost Index) and an inequitable capital allocation centralized around the district capital, Gido. Operationally, execution is hindered by extreme fiscal dependency, top-down communication that overrides grassroots planning forums (Musrenbang), and the systematic exclusion of local laborers by private contractors, triggering community alienation. To foster sustainable community welfare, local administrations must explicitly synchronize connectivity projects with economic empowerment. This study strongly recommends shifting fiscal priorities toward equitable rural network distribution, legally mandating local workforce quotas in private construction contracts, and adopting adaptive engineering designs to mitigate local environmental hazards.